Utility of automated cardiac chamber volumetry by nongated CT pulmonary angiography for detection of pulmonary hypertension using the 2018 updated hemodynamic definition - Melzig, Claudius; Do, Thuy; Egenlauf, Benjamin; Fink, Matthias A.; Grünig, Ekkehard; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Rengier, Fabian (American journal of roentgenology, 2022)
: - - BACKGROUND. Noninvasive tests for pulmonary hypertension (PH) are needed to help select patients for diagnostic right heart catheterization (RHC). CT pulmonary angiography (CTPA) is commonly performed for suspected PH. - - OBJECTIVE. The purpose of this study was to assess the utility of CTPA-based cardiac chamber volumetric measurements for the diagnosis of PH in comparison with echocardiographic and conventional CTPA parameters, with the 2018 updated hemodynamic definition used as reference. - - METHODS. This retrospective study included 109 patients (72 women and 37 men; median age, 68 years) who underwent nongated CTPA, transthoracic echocardiography, and RHC for the workup of suspected PH between August 2013 and February 2016. Two radiologists independently used automated 3D segmentation software to determine the volumes of the right ventricle (RV), right atrium (RA), left ventricle (LV), and left atrium (LA) and also measured the axial diameters of the cardiac chambers, main pulmonary artery, and ascending aorta. Interobserver agreement was assessed, and mean values were obtained; one observer repeated volumetric measurements to assess intraobserver agreement. ROC analysis was used to assess diagnostic performance for the detection of PH. A multivariable binary logistic regression model was established. - - RESULTS. A total of 60 of 109 patients had PH. Intra- and interobserver agreements were excellent for all volume measurements (intraclass correlation coefficients, 0.935-0.999). In patients with PH versus those without PH, RV volume was 172.6 versus 118.1 mL, and RA volume was 130.2 versus 77.0 mL (both p < .05). Cardiac chamber measurements with the highest AUC for PH were the RV/LV volume ratio and RA volume (both 0.791). Significant predictors of PH20 (as defined using the 2018 hemodynamic definition from the Sixth World Symposium on Pulmonary Hypertension) after adjustment for age, sex, and body surface area included RV volume per 10 mL (odds ratio [OR], 1.21), RA volume per 10 mL (OR, 1.27), RV/LV volume ratio (OR, 2.91), and RA/LA volume ratio (OR, 11.22). Regression analysis yielded a predictive model for PH that contained two independent predictors: echocardiographic pulmonary arterial systolic pressure and CTPA-based RA volume; the model had an AUC of 0.898, sensitivity of 83.3%, and specificity of 85.7%. - - CONCLUSION. Automated cardiac chamber volumetry using nongated CTPA, particularly of the RA, provides incremental utility relative to echocardiographic and conventional CTPA parameters for diagnosis of PH. - - CLINICAL IMPACT. Automated volumetry of cardiac chambers based on nongated CTPA may facilitate early noninvasive detection of PH, identifying patients who warrant further evaluation by RHC.